“Bullying y comportamiento social en los estudiantes de la Escuela de Educación Básica “Fe y Alegría” Riobamba. 2016-2017” - Elizabeth Fernanda, Orozco Martínez. (2017)
This research was carried out at “”Fe y Algeria” Elementary Scholl in the city of Riobamba during the 2016-2017 school year. Students of the sixth year of basic education parallel A and B participated in this program whose purpose was to determine bullying and its association with social behavior during the indicated period. First,, the Bullying Concept was established, and then the social behavior was identified and finally the cases of bullying were identified and its association in the social behavior. This research study was justified by the predominance of the problem and the need for a correct institutional coexistence between peers for a proper integral development. All the information of the research was obtained through is descriptive and non-experimental. The population was 68 students, and the sample was non-probabilistic intentionally because it included all the students. The technique used was two surveys; the first was a questionnaire to establish the manifestations of bullying which constituted 14 closed questions with the options of (Yes-No), and the second questionnaire corresponded to the social behavior which constituted 10 questions with the options of (Always, At times, and Never).Concluding that bullying has a dominant association in the social behavior of students.